Effect of waterjet cleaning parameters during paint removal operation on automotive steel components - M. N., Mat Nawi; Alzaghir, A. F.; H., Husin; Gebremariam, M. A.; Mohd Azmir, Mohd Azhari (Penerbit UMP, 2023)
The automotive industry is expanding quickly, and each year, many vehicles are produced with beautiful paints. Increases in the number of end-of-life or old vehicles will occur as a result of uncontrolled growth in the number of manufactured vehicles. Recycling car parts is therefore necessary in the automotive industry specially to beautify the appearance of old vehicles with new paint. Waterjet cleaning is one of the most contemporary techniques frequently employed to guarantee uniform paint removal with no secondary pollutions. Study on waterjet cleaning parameters mostly focuses on pressure, traverse rate, and standoff distance. However, there are other new parameters associated with waterjet cleaning process namely number of cleaning passes and overlap rate which shows improvement in paint removal but lack in literature reviews. In the present study, paint is removed using the abrasive waterjet (AWJ) and plain waterjet (PWJ) paint removal techniques from parts made for automobiles in order to examine cleaning characteristics such as effectiveness and surface roughness. The findings indicated that AWJ cleaning process was more effective at cleaning than PWJ, which had a smaller cleaning capacity. However, AWJ cleaning process resulted in a rougher surface due to complete removal of paints as well as erosion of the substrate material. A better control of AWJ cleaning process may result in more efficient of paint removal without damaging the substrate material.